Frost hardiness of almond flower buds during dormancy - Keleta, Belay Teweldemedhin; Békefi, Zsuzsanna; Bakos, József László; Örsi, Dorottya; Szalay, László (Acta Biologica Szegediensis, 2023)
Frost hardiness of flower buds of twenty almond genotypes was investigated in five dormancy periods by determining LT50 values after artificial freezing tests. The main aim of our work was modelling the changing of frost hardiness of the observed accessions during dormancy and assessing the potential best frost tolerance of them. The effect of genotype and year had significant impact on frost hardiness of flower buds. The potential frost hardiness of accessions has been characterised by LT50 values of flower buds averaged of the bests of the four years. ‘Sóskút 96/5’ was the most sensitive with -17.16 °C, and ‘Tétényi keményhéjú’ was the most frost hardy with -21.08 °C in averaged of years, but both showed lower and higher frost tolerance as well in different years. Flower buds were most frost-tolerant in December and January but did not achieve the same frost resistance every year. From this, we conclude that temperature plays an important role in the hardening process of them. From the aspect of safe yield, frost hardiness of flower buds is an important trait of cultivars, because Hungary is situated at the northern part of economical almond growing area. Our work contributes to facilitating practical considerations in orchard planning.